Gestión del proceso administrativo mediante el plan estratégico institucional, en la unidad educativa Fiscomisional José María Vélaz, de la parroquia Eloy Alfaro, cantón Latacunga provincia de Cotopaxi, en el período 2016-2020. - Tobar Rubio, Marco Vinicio (2017)
The researching work analyzes the management of the administrative process of the José María Vélaz Fiscomisional Educational Unit, therefore à field-based, bibliographical-documentary research was applied, the study population were the managers, teachers and students of the educational institution, Denoting that the need to make a strategic plan that allows him to better manage the resources of the educational establishment. The methodology that was used in the survey of the information through the technique of the survey. For that, the situational diagnosis of the educational unit was carried out, focusing on the training of teachers, infrastructure, institutional resources, academic level, with the establishment of priority lines and strategic objectives in the medium and long term. With the design of the strategies according to the priority lines that will allow the Educational Unit "Jose Maria Vélaz Fiscomisional" strategically improve the administrative processes, through a strategic direction.